(untitled) (Damu Journal of Sport Sciences, 2025)
The strategy of differentiated instruction is considered one of the fundamental pillars in modern education, aiming to meet the diverse needs and requirements of students. This strategy embodies the concept of integration between teaching and learning, tailoring educational content to suit individual students, thereby enhancing their understanding and motivating them to achieve their maximum potential. The emphasis on using the strategy of differentiated instruction is growing in the field of artistic gymnastics, where it addresses individual differences among students and caters to them accordingly. The research problem revolves around the challenging nature of gymnastics skills that require high concentration, considering the significant individual differences among students. The researcher decided to address this issue by implementing the strategy of differentiated instruction in the process of teaching skills through intelligence tests. The research community consisted of second-stage students at the University of Al-Qadisiyah/Faculty of Physical Education and Sports Science for the academic year 2022-2023. The research sample included 18 students divided into control and experimental groups, with the control group following the teacher's curriculum and the experimental group following the researcher's curriculum.